ANALISIS ASOSIASI SEMBURAN RADIO MATAHARI TIPE III DENGAN FLARE SINAR-X DAN FREKUENSI MINIMUM IONOSFER - - Suratno; Sri Suhartini (Lembaga Penerbangan dan Antariksa Nasional, 2011)
The type III solar radio bursts is an indicator of solar X-ray flare phenomena. The effect of solar X-ray flares to the ionospheric layer is the increasing of minimum frequency (fmin) which indicates the absorption of incoming high frequency (HF) radio wave. Further impact is a disturbance of high frequency radio communications. The number and flux density of type III bursts and X-ray flare can used as an information of ionospheric disturbance possibility. The correlation analysis shows that the number of X-ray flare is related to the number of ionospheric absorption and the time duration of these absorption. The serial event of type III bursts and solar X-ray flare occures during February 6th to 12th, 2010 are an example cases of the early warning of possibility of radio communications disturbances. Key Words:Solar radio bursts, X-ray flare, Radio communication disturbance